494 Placebo-Controlled, Double-Blind, Randomized Withdrawal Study of Lower-Sodium Oxybate in Adults With Idiopathic Hypersomnia. (3rd May 2021) - Dauvilliers, Yves; Arnulf, Isabelle; Foldvary-Schaefer, Nancy; Chandler, Patricia; Parvataneni, Rupa; Chen, Dan; Skobieranda, Franck; Bogan, Richard
Abstract: Introduction: Idiopathic hypersomnia (IH) is a rare central hypersomnolence disorder characterized by excessive daytime sleepiness, prolonged nighttime sleep, and sleep inertia. No US/EU medication is approved for treatment of IH. Lower-sodium oxybate (LXB; Xywav™; previously designated JZP-258) is a novel oxybate treatment with 92% less sodium than sodium oxybate (Xyrem®). The efficacy and safety of LXB was evaluated in adults with IH. Methods: Eligible participants aged 18–75 years with IH began once- or twice-nightly LXB treatment entering an open-label titration and optimization period (10–14 weeks), followed by a 2-week, open-label, stable-dose period (SDP); they were then randomized to placebo or to continue LXB treatment during a 2-week, double-blind, randomized withdrawal period (DBRWP). The primary efficacy endpoint was change in Epworth Sleepiness Scale (ESS) score; key secondary endpoints were proportion of participants who reported worsening (minimally/much/very much worse) on Patient Global Impression of Change (PGIc) and change in Idiopathic Hypersomnia Severity Scale (IHSS) score, all from end of SDP to end of DBRWP. Results: The study enrolled 154 participants (mean±SD age, 40±14 years; 68% female; mean±SD ESS, 16±3.6); mean±SD dose was 6.0±1.6 g/night. Mean±SD ESS score (n=115) decreased over open-label titration/optimization (15.7±3.8 at baseline, 9.8±4.5 at week 4, and 6.1±4.0 at the end of the SDP). At the end of the DBRWP, significant worsening was observed in participants randomized to placebo, compared with maintenance of improvement in participants randomized to continue LXB, in ESS scores (n=115; LS mean difference [95% CI] in change from SDP, −6.51 [−7.99, −5.03]; P<0.0001), in the PGIc (88.1% for placebo vs 21.4% for LXB; P<0.0001), and in IHSS scores (estimated median difference [95% CI], −12.00 [−15.0, −8.0]; P<0.0001). Common adverse events (AEs) included nausea (21.4%), headache (16.2%), anxiety (14.9%), dizziness (11.7%), insomnia (11.7%), and vomiting (10.4%). Serious AEs occurred in 4 participants (non-cardiac chest pain, rhabdomyolysis, syncope, and nephrolithiasis/pyelonephritis); none were reported related to study drug. Conclusion: In participants with IH, LXB demonstrated a clinically meaningful effect on excessive daytime sleepiness, self-reported global change, and overall IH symptom severity. The overall safety profile was consistent with that of LXB in narcolepsy. Support (if any): Jazz Pharmaceuticals